Translation and Psychometric Testing of the Thai COVID-19 Vaccine Literacy Scale - Maneesriwongul, Wantana; Butsing, Nipaporn; Visudtibhan, Poolsuk Janepanish; Leelacharas, Sirirat; Kittipimpanon, Kamonrat (Pacific Rim International Journal of Nursing Research, 2021)
Vaccine literacy is positively associated with vaccination, so assessment of COVID-19 vaccine literacy is essentially needed. This study translated the COVID-19 Vaccine Literacy Scale, English version into Thai, and tested the psychometric properties of the Thai version (Thai COVID-19 VL Scale). A cross-sectional survey was conducted online. Data comprising 1,002 participants aged 18 years or older were analyzed using exploratory factor analysis and confirmatory factor analysis to identify factor structure and construct validity of the Thai COVID-19 VL Scale. Also, construct validity using the known-groups technique and internal consistency reliability were employed to test the scale. According to the exploratory factor analysis, the results revealed that the 12-item scale consisting of two factors, Interactive/critical vaccine literacy and Functional vaccine literacy explained 58.1% of the total variance. The confirmatory factor analysis indicated that the measurement model had relatively goodness of fit with the data. Cronbach’s alpha coefficients were 0.81 for the overall scale, 0.85 and 0.86 for both subscales, respectively. By using a known-groups technique, it was revealed that the participants who were vaccinated against COVID-19 had significantly higher vaccine literacy scores than those who intended and who were not sure/ not willing to get vaccination. This study indicated that the Thai COVID-19 VL Scale has adequate validity and reliability for assessing vaccine literacy among Thai people. It has the potential for nurses to identify people with low vaccine literacy so that a public health intervention can be targeted more specifically to enhance vaccine literacy and increase vaccine uptake in Thailand.